MORPHOPEDOLOGICAL STUDY OF THE ARROIO GUASSUPI WATER BASIN, SÃO PEDRO DO SUL – RIO GRANDE DO SUL (RS): BASIS FOR UNDERSTANDING EROSION PROCESSES - Marciel Lohmann; Leonardo José Cordeiro Santos (Sociedade & Natureza)
Soil erosion represents one of the most serious environmental problems, jeopardising food production in terms of quality and quantity. It is, therefore, strictly linked to scarcity and starvation. Bertoni & Lobardi Neto (1990) point out that eroded lands have had their productive capacity reduced, making the struggle against erosion fundamental in some parts of the world.In Brazil, around 600 million tons of agricultural soil are lost per year (BAHIA et al 1992). According to Infanti Jr & Fornasari Filho (1998), the phenomena related to erosion formation are caused by two main types of factors or agents: the anthropogenic type, such as deforestation, mining activities and ways of using and occupying the soil (agriculture, construction works, urbanisation, etc.), which precipitates the erosion process immediately or after some time; and the natural type, which will determine the intensity of the processes. In this group, we can highlight the rain, vegetation cover, relief, soils and bedrock. When the erosion process takes place under natural or non-disturbed conditions, a permanent balance is established, and no greater damage occurs. However, when this balance is broken, erosion creates serious problems, not only in agriculture, by generating a gradual loss of productivity, but also in the management of water resources, contaminating them with sediment.